Identification of cis-regulatory modules encoding temporal dynamics during development - Potier, Delphine; Seyres, Denis; Guichard, Céline; Iche-Torres, Magali; Aerts, Stein; Herrmann, Carl; Perrin, Laurent (BMC genomics, 2014)
Developmental transcriptional regulatory networks are circuits of transcription factors (TFs) and cis-acting DNA elements (Cis Regulatory Modules, CRMs) that dynamically control expression of downstream genes. Comprehensive knowledge of these networks is an essential step towards our understanding of developmental processes. However, this knowledge is mostly based on genome-wide mapping of transcription factor binding sites, and therefore requires prior knowledge regarding the TFs involved in the network.